2021
DOI: 10.21037/apm-21-165
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multi-dimensional postpartum visits on increasing the breastfeeding rate of parturients with inverted nipple: a randomised study

Abstract: Background: Postpartum breastfeeding is an effective guarantee for the healthy growth of newborns.Vigorously promoting breastfeeding has substantial benefits for the physical and mental health of mothers and babies, and can also benefit the entire society. The purpose of this study was to explore the effect of multi-dimensional postpartum visits (MDPV) applied to parturients with inverted nipple on improving breastfeeding rates.Methods: A total of 114 parturients with inverted nipples who gave birth in the Dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Historically, corrective surgery was reserved for the severely invaginated nipples (grade 3) that are not amenable to manual extraction, whereas non-surgical methods were indicated for less severe inversion (grades 1 or 2). Non-surgical interventions are several with variable rates of breastfeeding success and/or correction of nipple inversion [16][17][18][19][20]. Hoffman exercises and Woolwich breast shields for example were investigated in a clinical trial by Alexander, et al, and were found to have no effect on nipple anatomy or breastfeeding rates [16].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, corrective surgery was reserved for the severely invaginated nipples (grade 3) that are not amenable to manual extraction, whereas non-surgical methods were indicated for less severe inversion (grades 1 or 2). Non-surgical interventions are several with variable rates of breastfeeding success and/or correction of nipple inversion [16][17][18][19][20]. Hoffman exercises and Woolwich breast shields for example were investigated in a clinical trial by Alexander, et al, and were found to have no effect on nipple anatomy or breastfeeding rates [16].…”
Section: Introductionmentioning
confidence: 99%